2022
DOI: 10.1021/acsami.2c10640
|View full text |Cite
|
Sign up to set email alerts
|

Tafel-Kinetics-Controlled High-Speed Switching in a Electrochemical Graphene Field-Effect Transistor

Abstract: Graphene field-effect transistors (FETs) have attracted tremendous attention owing to the single-atomic-layer thickness and high electron mobility for potential applications in next-generation electronics. With regards to switching methodology, the electric-field-induced metal−insulator transition offers a new strategy to produce a large on/off current ratio through reversible electrochemical hydrogenation of the graphene channels. Therefore, the performance of such electrochemical graphene FETs greatly relies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…For devices used in Raman spectroscopy measurements, a long strip of platinum foil was used as the gate electrode instead. The detailed assembly procedures and electrolyte injection were reported in our previous works. , The hydrogen ion electrolyte consisted of 0.4 mol/L bis­(trifluoromethane)­sulfonamide (HTFSI) in liquid poly­(ethylene glycol) (PEG) with an average M n of 600. The PEG was heated to 100 °C for a few hours followed by vacuum evacuation to remove residual moisture.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For devices used in Raman spectroscopy measurements, a long strip of platinum foil was used as the gate electrode instead. The detailed assembly procedures and electrolyte injection were reported in our previous works. , The hydrogen ion electrolyte consisted of 0.4 mol/L bis­(trifluoromethane)­sulfonamide (HTFSI) in liquid poly­(ethylene glycol) (PEG) with an average M n of 600. The PEG was heated to 100 °C for a few hours followed by vacuum evacuation to remove residual moisture.…”
Section: Methodsmentioning
confidence: 99%
“…When V G returns to −1 V, the graphene is dehydrogenated, and I DS promptly recovers back to the LRS. Notably, our previous work has demonstrated that such an on/off ratio can reach 10 8 with high reversibility for ≤1 million switching cycles, , which presents exciting implications for the development of advanced devices that require high stability and specificity through the delicate control of C–H bond concentration in graphene.…”
mentioning
confidence: 99%
See 1 more Smart Citation